Analisis Pemikiran Ekonomi Ibnu Khaldun dan Relevansinya Terhadap Sistem Ekonomi Modern - Hayati, Fitri; Harahap, Faris Andrawika; Santika Siregar, Imel; Auliya Lubis, Niswa; Siti Nurhalimah; Yusliani, Yusliani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the economic thought of Ibn Khaldun and its relevance to the modern economic system. Employing a qualitative approach through library research and document analysis, the study examines key concepts in Al-Muqaddimah, such as the economic cycle theory, market mechanisms, the role of the state, and distributive justice advocated by Ibn Khaldun. The findings reveal that Ibn Khaldun’s economic thought holds significant relevance in addressing modern economic challenges, particularly social inequality, wealth redistribution, and market regulation. Empirical studies on the implementation of zakat systems in Malaysia and modern economic theories like Keynesianism and institutional economics support these findings. Therefore, integrating Ibn Khaldun’s classical economic values into contemporary economic policies can enhance the stability, justice, and sustainability of the global economic system. This research contributes to enriching Islamic economic literature and offers practical solutions for inclusive and equitable economic development.